Age and Factors Associated with Clinical and Radiological Outcomes of Surgical Containment in Legg-Calve-Perthes Disease - Adulyanukosol, MD, Varinthorn; Lewsirirat, MD, Supphamard; Chinvattanachot, MD, Guntarat (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To determine the factors associated with clinical and radiological outcomes in patients with Legg-Calve-Perthes disease (LCPD) treated with containment methods. Methods: This retrospective cohort study was conducted from 2007 – 2017. Patients diagnosed with LCPD in the fragmentation stage and treated using surgical containment methods were included. Study factors were age at diagnosis, preoperative radiographs analyzed for lateral pillar staging and Catterall classification. Outcome measurements were final follow-up radiograph, classified using modified Stulberg grading, and final clinical outcome, classified by Harris Hip Score. Results: We analyzed 44 hips. The average age of subjects during diagnosis and follow-up was 8.1 and 12.7 years, respectively. The average length of follow-up was 58.6 months. Nineteen hips were evaluated as “good” (Stulberg I or II), 22 hips as “fair” (Stulberg III), and four hips as “poor” (Stulberg IV); no hips were classified as Stulberg V. Although not significant, the combination of Salter osteotomy and femoral varus osteotomy yielded better outcomes than varus osteotomy alone in the group >8 years old (p=0.247). The median age of 7 (7 – 8) years old was correlated with “good to excellent” Harris Hip Score while median age of 9 years was significantly correlated with the score of “fair” and “poor” (p=0.018). Lateral pillar A and B yielded significantly better results than lateral pillar C (p=0.014). Conclusion: The containment methods demonstrated favorable outcomes when treating patients < 9 years. Lateral pillars A and B had good end results. Combined pelvic and femoral osteotomy can improve radiographic and clinical outcomes.